NEURO-RAWSHAN CLASSIFICATION MODEL OF FORMATION OF MULTIFACTOR INDICATORS OF POPULATION'S STANDARD OF LIVING (Marketing Journal, 2025)
This paper examines the development of a multifactorial system of indicators for assessing and improving a personʼs standard of living based on a neural network classification model. The study developed an integrated indicator system combining demographic, economic, social, and infrastructure indicators. Furthermore, artificial neural networks and fuzzy logic elements were combined to account for uncertainty, systematicity, and complex nonlinear relationships between indicators.
Keywords: standard of living; multifactor indicators; fuzzy classification; fuzzy clustering; fuzzy C -means; neuro -fuzzy classification; neuro -fuzzy model